Testimonianze - Maurizio Fabbri; Rita Fadda; Mario Gennari (Firenze University Press, 2019)
"Studi sulla Formazione" plays an important role in Italy for pedagogical research: it hosts articles by international authors from different research fields. The testimonies of three important authors show the contemporary relevance of the journal in pedagogical research and its vocation for dialogue.